2019
DOI: 10.1155/2019/2031312
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Predictive Fault‐Tolerant Control for Time‐Delay Nonlinear Systems with Partial Actuator Failures

Abstract: A fuzzy predictive fault-tolerant control (FPFTC) scheme is proposed for a wide class of discrete-time nonlinear systems with uncertainties, interval time-varying delays, and partial actuator failures as well as unknown disturbances, in which the main opinions focus on the relevant theory of FPFTC based on Takagi-Sugeno (T-S) fuzzy model description of these systems. The T-S fuzzy model represents the discrete-time nonlinear system in the form of the discrete uncertain time-varying delay state space, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 52 publications
(65 reference statements)
0
11
0
Order By: Relevance
“…Shi et al [15] proposed a robust constraint model to predict fault-tolerant control for industrial processes with actuator fault. Shi et al [16] proposed a fuzzy predictive fault-tolerant control method for nonlinear system with partial actuator failures. In reference [13][14][15][16], in view of the problem of partial actuator failure, the control method adopted is to introduce the failure factor into the controller design to overcome the effect of actuator failure on the system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shi et al [15] proposed a robust constraint model to predict fault-tolerant control for industrial processes with actuator fault. Shi et al [16] proposed a fuzzy predictive fault-tolerant control method for nonlinear system with partial actuator failures. In reference [13][14][15][16], in view of the problem of partial actuator failure, the control method adopted is to introduce the failure factor into the controller design to overcome the effect of actuator failure on the system.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al [16] proposed a fuzzy predictive fault-tolerant control method for nonlinear system with partial actuator failures. In reference [13][14][15][16], in view of the problem of partial actuator failure, the control method adopted is to introduce the failure factor into the controller design to overcome the effect of actuator failure on the system. Furthermore, time delay is also an important factor affecting system stability and control performance.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of these results proves that MPC can effectively deal with the time delay problem in the system, but these articles do not consider how to deal with the problem of actuator failure in the case of time delay. And rare researches [24,25] about integrated FTC with MPC have been presented for system with time-delay, failure and other issues. It can be found that the reliable control is applied in references [25,26], which is quite appropriate for system with frequent failures.…”
Section: Introductionmentioning
confidence: 99%
“…And rare researches [24,25] about integrated FTC with MPC have been presented for system with time-delay, failure and other issues. It can be found that the reliable control is applied in references [25,26], which is quite appropriate for system with frequent failures. Remarkably, as the science technique develops, some advanced devices are designed and developed so that the possibility of fault becomes lower.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation